2007
DOI: 10.1007/s11113-007-9031-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of infant and child mortality in Kenya: an analysis controlling for frailty effects

Abstract: In this paper, Weibull unobserved heterogeneity (frailty) survival models are utilized to analyze the determinants of infant and child mortality in Kenya. The results of these models are compared to those of standard Weibull survival models. The study particularly examines the extent to which child survival risks continue to vary net of observed factors and the extent to which nonfrailty models are biased due to the violation of the statistical assumption of independence. The data came from the 1998 Kenya Demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
102
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(108 citation statements)
references
References 38 publications
6
102
0
Order By: Relevance
“…We observed that the risk of infant mortality is about 5 times more likely for children of mother greater 35 years old at their first birth compared with children of whose their mother's age as at the time of their first birth was less than 20 years. This is in consistent with the study in Kenya by Omariba [9]. This high effect of maternal age at first birth to infant mortality may be due to physiological and sociopsychological factors.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We observed that the risk of infant mortality is about 5 times more likely for children of mother greater 35 years old at their first birth compared with children of whose their mother's age as at the time of their first birth was less than 20 years. This is in consistent with the study in Kenya by Omariba [9]. This high effect of maternal age at first birth to infant mortality may be due to physiological and sociopsychological factors.…”
Section: Discussionsupporting
confidence: 93%
“…Mortality in human population follow Weibull, because it is generally high in the first years of life, it declines in other ages of childhood, then increasing slowly in adult ages to old age [17]. Based on this point, many researches on childhood mortality used Weibull model [9,11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations